Analysis of bisabolocurcumin ether (a terpene-conjugated curcuminoid) and three curcuminoids in Curcuma species from different regions by UPLC-ESI MS/MS and their in vitro anti-inflammatory activities - Rui Li (Journal of Functional Foods, 2019)
The terpene-conjugated curcuminoid bisabolocurcumin ether (BCE) is a newly identified bioactive curcuminoid, but its abundance in different Curcuma species is unknown. We developed an efficient MCI-gel-based method to purify BCE from C. longa, and established BCE fragmentation pathways under ESI-MS/MS. The abundances of BCE curcumin, demethoxycurcumin, and bisdemethoxycurcumin determined in C. longa rhizomes from Thailand, Indonesia, and China, C. longa roots from China, and C. phaeocaulis rhizomes from China. The abundance of the four compounds varied significantly, not only among different Curcuma species and cultivation regions, but also among different parts of the same species. BCEs were only detected in C. longa from Thailand and China, and in C. longa roots. C. longa from Thailand showed the highest abundance of curcuminoid [average 85.07 mg/g] and BCE [average 0.64 mg/g]. Moreover, BCE and three curcuminoids showed anti-inflammatory potential, as evidenced by the inhibition of lipopolysaccharide-induced production of nitric oxide in macrophages.